2011
DOI: 10.1027/1016-9040/a000029
|View full text |Cite
|
Sign up to set email alerts
|

Celebrity Worship Among University Students in Malaysia

Abstract: The present study examined conceptual issues surrounding celebrity worship in a Malay-speaking population. In total, 512 Malay and 269 Chinese participants from Malaysia indicated who their favorite celebrity was and completed the Celebrity Attitude Scale (CAS) as well as a range of demographic items. Results showed that the majority of Malay and Chinese participants selected pop stars and movie stars as their favourite celebrities, mirroring findings in Western settings. In addition, exploratory factor analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 44 publications
(88 reference statements)
4
11
0
Order By: Relevance
“…While some participants expressed that celebrity products (e.g., feel impressed with the celebrities' music or performance) and personal characteristics of the celebrity (e.g., feel appreciation from the celebrities or the celebrities exhibit positive attitudes) were the contributing factors to keep their loyalty towards a celebrity, others encountered peer influence when they were first attracted to a celebrity. This concurs with the absorption-addiction model which suggests that the first level of celebrity worship is entertainment-social whereby people would be attracted to the celebrity because of these 2 factors (Hyman & Sierra, 2007, Swami et al, 2010. Also, at this level, participants devoted much time and energy to their celebrities because of the physiological characteristics of the celebrity like good looks and good voices.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…While some participants expressed that celebrity products (e.g., feel impressed with the celebrities' music or performance) and personal characteristics of the celebrity (e.g., feel appreciation from the celebrities or the celebrities exhibit positive attitudes) were the contributing factors to keep their loyalty towards a celebrity, others encountered peer influence when they were first attracted to a celebrity. This concurs with the absorption-addiction model which suggests that the first level of celebrity worship is entertainment-social whereby people would be attracted to the celebrity because of these 2 factors (Hyman & Sierra, 2007, Swami et al, 2010. Also, at this level, participants devoted much time and energy to their celebrities because of the physiological characteristics of the celebrity like good looks and good voices.…”
Section: Discussionsupporting
confidence: 85%
“…As defined by Maltby et al (2002), a score at or above the scale midpoints on the three subscales of the CAS is considered as a celebrity worshiper. This scale has been validated in different countries such as the United States, United Kingdom and Malaysia (Maltby et al, 2002;McCutcheon, et al, 2002;Swami et al, 2010).…”
Section: Approach and Research Designmentioning
confidence: 99%
“…Similar to previous studies (Griffith et al., 2013; Sheridan et al., 2007; Swami et al., 2011), the most frequently chosen categories for participants’ favorite celebrity were singers or musicians and actors/actresses.…”
Section: Discussionsupporting
confidence: 55%
“…(2003) (i.e., 27% scoring high on the two problematic dimensions). One possible explanation could be that the proportion of male participants was very high in the present sample, and some studies reported that females are more likely to become fascinated with celebrities than males (Reyes et al., 2016; Swami et al., 2011). However, due to the lack of cutoff points that are based on empirical findings, these prevalences should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation